2008
DOI: 10.3233/ch-2008-1124
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic postconditioning reduces peroxide formation, cytokine expression and leukocyte activation in reperfusion injury after abdominal aortic surgery in rat model

Abstract: Objective: We studied the protective effects of ischaemic postconditioning (PS) on ischemia-reperfusion injury of the lower extremities in a rat model of abdominal aortic intervention. We aimed to examine the evoked oxidative stress, cytokine expression and leukocyte activation after revascularisation surgery.Methods: Anesthetized animals (48 Whistar rats) underwent a 60 min infrarenal aorta cross-clamping. After the ischaemic period, an intermittent 4 times 15 s reperfusion -15 seconds ischaemic episodes -wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Furthermore, development of IR has been shown to cause a remarkable increase in the serum level of tumor necrosis factor alpha (TNF-α), mainly through release from activated Kupffer cells [ 9 , 10 ]. Other studies have shown TNF-α to further induce cytokines and production of granulocyte colony-stimulating factor, which in turn further enhance Kupffer cell activation and promote neutrophil infiltration in the liver [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, development of IR has been shown to cause a remarkable increase in the serum level of tumor necrosis factor alpha (TNF-α), mainly through release from activated Kupffer cells [ 9 , 10 ]. Other studies have shown TNF-α to further induce cytokines and production of granulocyte colony-stimulating factor, which in turn further enhance Kupffer cell activation and promote neutrophil infiltration in the liver [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after the hepatic ischemia and reperfusion injury (1-6 hours), the Kupffer cells are activated and release the pro-inflammatory cytokines, such as tumor necrosis factor alpha (TNF α) and interleukin-1 beta (IL-1β). These cytokines have dual role: over range expression of TNFα and IL-1β can induce more production of cytokines and granulocyte colony-stimulating factor, which enhance Kupffer cells activation and promote neutrophil infiltration in microcirculation of liver 6 , 7 , then aggravate hepatic sterile inflammation after ischemia and reperfusion. On the other hand, TNFα and IL-1 are indispensable for liver regeneration 8 .…”
Section: Introductionmentioning
confidence: 99%
“…KC is the major source of oxidative stress substrates in response to ischemic injury 21,22 , releasing inflammatory cytokines, such as TNF-α and IL-β, which contributes to ischemic hepatocytes injury. It’s well known that LPS can induce TLR4 activation followed by inflammatory cytokine release 23,24 , which also results in KCs activation and hepatic inflammatory injury 25 .…”
Section: Discussionmentioning
confidence: 99%